Land use, mobility and accessibility in dualistic urban China: A case study of Guangzhou. (November 2017) - Li, Si-ming; Liu, Yi
Abstract: The concept of accessibility has been widely employed to understand the jobs-housing relationship in US cities. However, relevant studies in Chinese cities are rare. Little attention has been paid to accessibility modelling, variations among population groups, and the influence of land use arrangement and transport infrastructure in Chinese cities. To address this deficiency, the present paper provides measures on the job accessibility of workers with different hukou status in Guangzhou. The study yields the following findings: 1) inner-city districts have better job accessibility compared to suburban areas; 2) local hukou workers have significantly higher job accessibility than non-local hukou workers; 3) job suburbanization seems not to be effective in improving job accessibility or narrowing the gap between local and non-local hukou workers; and 4) investment in public transport would significantly improve the mobility and job accessibility of non-local hukou workers and help to alleviate accessibility inequality. Highlights: Hukou influences labour and housing market segmentations and commuting patterns and job accessibility in Chinese cities. There is a concentric pattern of job accessibility in Guangzhou. Local hukou workers have greater job accessibility than non-local hukou workers. The paradox between inferior job accessibility and lower commuting cost could be attributed to hukou -related constraints. Mobility-oriented policies are more effective in alleviating accessibility inequality than land-use-oriented policies.